Selective Leaching of Dissolved Organic Matter From Alpine Permafrost Soils on the Qinghai-Tibetan Plateau - Wang, Yinghui; Xu, Yunping; Spencer, Robert G. M.; Zito, Phoebe; Kellerman, Anne; Podgorski, David; Xiao, Wenjie; Wei, Dandan; Rashid, Harunur; Yang, Yuanhe (Journal of Geophysical Research: Biogeosciences, 2018)
Ongoing global temperature rise has caused significant thaw and degradation of permafrost soils on the Qinghai-Tibetan Plateau (QTP). Leaching of organic matter from permafrost soils to aquatic systems is highly complex and difficult to reproduce in a laboratory setting. We collected samples from natural seeps of active and permafrost layers in an alpine swamp meadow on the QTP to shed light on the composition of mobilized dissolved organic matter (DOM) by combining optical measurements, ultrahigh-resolution Fourier transform ion cyclotron resonance mass spectrometry, radiocarbon (C-14), and solid-state C-13 nuclear magnetic resonance spectroscopy. Our results show that even though the active layer soils contain large amounts of proteins and carbohydrates, there is a selective release of aromatic components, whereas in the deep permafrost layer, carbohydrate and protein components are preferentially leached during the thawing process. Given these different chemical characteristics of mobilized DOM, we hypothesize that photomineralization contributes significantly to the loss of DOM that is leached from the seasonally thawed surface layer. However, with continued warming, biodegradation will become more important since biolabile materials such as protein and carbohydrate are preferentially released from deep-layer permafrost soils. This transition in DOM leachate source and associated chemical composition has ramifications for downstream fluvial networks on the QTP particularly in terms of processing of carbon and associated fluxes.